An Econometric Study of Recruitment Marketing in the U.S. Navy - Hanssens, Dominique M.; Levien, Henry A. (Management Science, 1983)
Since the abolishment of the mandatory draft the U.S. Navy, along with the other services, has engaged in aggressive marketing strategies in order to attract a sufficient number of qualified individuals to volunteer enlistment. The purpose of this study is to investigate the effectiveness of these efforts, primarily advertising and personal selling, within the general framework of the recruiting environment. The study uses insights into the recruiting process, provided by the Navy Recruiting Command, along with principles of economics and marketing to develop an econometric model of recruiting performance. The parameters of the model are then estimated on a monthly data base for the 43 Navy Recruiting Districts, from January 1976 to December 1978. The objective of the model is descriptive, i.e., it quantifies the effects of various environmental and marketing variables on three measures of recruiting performance: nationally generated leads, contracts for the delayed-entry program and direct-shipment contracts. The enlistment contracts refer to nonprior service males between 17 and 21 years old. The environmental variables in the models include economic factors such as unemployment rate and civilian income, sociodemographic variables such as urbanization, the proportion of blacks and high-school seniors in the target market, and local youth attitudes toward the Navy, and time-related factors such as seasonally and the GI Bill. The marketing efforts are national advertising expenditures in seven media, local advertising expenditures, recruiter strength and recruiter aid expenditures. The econometric models reveal that both environmental and marketing variables had significant impact on variations in recruiting performance over time and across recruiting districts. The specific response effects for leads and contracts are reported in the “discussion of results” section. The “conclusions” section integrates several of these results along three dimensions: the relative influence of environmental versus marketing variables on recruiting performance, differences in the response structures for leads, delayed-entry and direct-shipment contracts, the relative effectiveness of media advertising and personal selling.